A Prospective Randomized Controlled Trial Comparing Enoxaparin & Rivaroxaban for Venous Thromboembolism Prophylaxis in Orthopaedic Trauma. Issue 12 (December 2022) - John, Mitchell P.; Streufert, Benjamin D.; Downes, Katheryne; Chase, Collin B.; Mir, Hassan R.
Abstract : Objectives: To determine whether there is a difference in orthopaedic trauma patient medication satisfaction and adherence using an oral versus subcutaneous injectable anticoagulant for venous thromboembolism chemoprophylaxis. Design: Randomized controlled trial. Setting: Single academic Level 1 trauma center. Participants: One hundred twenty adult orthopaedic trauma patients with operative pelvic or lower extremity fractures were randomized and completed the study. Intervention: Three weeks of either the service standard 40 mg once daily enoxaparin versus trial medication 10 mg once daily rivaroxaban postoperatively. Main Outcome Measures: Patient satisfaction as measured by the Treatment Satisfaction Questionnaire for Medication (TSQM-9). Medication adherence as measured by the Morisky Medication Adherence Scale (MMAS-8). Results: Medication adherence was similar in both groups. Medication satisfaction was significantly higher in the oral rivaroxaban group based on the TSQM-9 and patient-reported data. Secondary outcomes found no significant difference in the incidence of bleeding events or clinically relevant venous thromboembolism. The enoxaparin group experienced more adverse medication-related events. The rivaroxaban medication regimen costs 7.5–10× less out of pocket for uninsured patients. Conclusion: The results of this randomized controlled trial demonstrate that patients with surgical orthopaedic trauma prefer an oral anticoagulant for postoperative venous thromboembolism chemoprophylaxis and suggest that rivaroxaban may be a viable option. Furthermore, large-scale studies are needed to confirm safety and efficacy for rivaroxaban in this population as a potential alternative to enoxaparin and aspirin. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.